Coexisting invasive gobies reveal no evidence for temporal and trophic niche differentiation in the sublittoral habitat of Lake Erhai, China. Issue 1 (7th September 2015) - Guo, Zhiqiang; Liu, Jiashou; Lek, Sovan; Li, Zhongjie; Zhu, Fengyue; Tang, Jianfeng; Britton, Robert; Cucherousset, Julien
Abstract: Niche differentiation facilitates the coexistence of species within a community through avoidance of competition via mechanisms involving spatial, temporal and/or trophic dimensions. Where invasive species coexist in their non‐native range, niche differentiation could allow their persistence at higher levels of abundance. Here, we tested whether there was temporal and/or trophic niche differentiation between two congeneric invasive goby species ( Rhinogobius cliffordpopei and Rhinogobius giurinus ) in the sublittoral habitat of Lake Erhai (south‐west China) through quantifying their diel and seasonal rhythm of locomotion activities, feeding activities and diet composition. Both species displayed two similar diel peaks in activity and two main feeding periods (6:00–10:00 and 18:00–22:00), with rhythms of locomotion and feeding activity not differing significantly between the species in each season. Their diets had a high degree of overlap, being primarily composed of macrozooplankton, aquatic insects and shrimp larvae, with no diel changes across the seasons. Thus, in this habitat, there was no clear temporal or trophic niche differentiation between the invasive congeners, indicating their coexistence with high temporal and trophic overlap. In conjunction with data from the littoral and profundal habitats, the gobies revealed different strategies across the habitats (e.g. spatial segregation, trophic niche differentiation) that minimised their competitive interactions and promoted their coexistence. This suggests that the interactions of invasive fishes during the integration into native communities can be context dependent, varying according to factors including habitat and the availability of food resources.